2011
DOI: 10.1007/s00270-011-0330-8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Stabilization of Impending Pathological Fracture of the Proximal Femur

Abstract: POPC for impending pathological fracture of the proximal femur seems to be a promising alternative for cancer patients who are not candidates for surgical stabilization. Further studies are required to confirm this preliminary experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 9 publications
1
36
0
2
Order By: Relevance
“…PIGSF is a novel technique for fracture fixation, which has recently been applied for the treatment of long bone, pelvic, and shoulder-girdle lesions in oncologic patients [16][17][18][19][20]. It offers advantages over conventional surgery including excellent visualisation of surrounding structures to avoid iatrogenic injury, and a rapid post-procedural recovery to minimise onco-therapeutic delay [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PIGSF is a novel technique for fracture fixation, which has recently been applied for the treatment of long bone, pelvic, and shoulder-girdle lesions in oncologic patients [16][17][18][19][20]. It offers advantages over conventional surgery including excellent visualisation of surrounding structures to avoid iatrogenic injury, and a rapid post-procedural recovery to minimise onco-therapeutic delay [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…It offers advantages over conventional surgery including excellent visualisation of surrounding structures to avoid iatrogenic injury, and a rapid post-procedural recovery to minimise onco-therapeutic delay [16][17][18][19]. The technique involves precise placement of co-axial cannulated screws over a guidewire placed perpendicular to the fracture/lesion under imaging guidance, securely anchoring the distal screw in good-quality bone [16][17][18]. Prior studies have demonstrated technical feasibility, safety, and good short/mid-term outcomes [16,17,19], which appear comparable to surgery [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cementoplasty is the injection of radio-opaque acrylic cement through a percutaneously inserted needle often with the use of CT guidance (93). Percutaneous osteosynthesis is the deployment of orthopedic hardware after insertion is guided with CT or cone-beam CT imaging (94).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%